Can scholarships provide equitable access to high-quality university education? Evidence from the Mastercard Foundation Scholars Program. (November 2019) - Cosentino, Clemencia; Fortson, Jane; Liuzzi, Sarah; Harris, Anthony; Blair, Randall
Highlights: The scholarship has large and positive impacts on access to higher education. The scholarship increases enrollment in bachelor's degree programs and studies abroad. One-third of recipients pursued graduate studies within 18 months of graduation. Half of students studying abroad returned to Africa within 18 months of graduation. Abstract: This paper estimates the impact of a scholarship program—the Mastercard Foundation Scholars Program—on access to university. Using propensity score matching, the analysis finds that the Program improves access to high-quality university studies among vulnerable, disadvantaged youth, mostly from Africa—increasing timely access to university, to higher levels of study, and to studies abroad. Half of scholarship recipients studying abroad return to Africa and a third pursue graduate studies within 18 months of graduation. The Program's collaborative approach holds promise for scaling up this and similar efforts to increase university participation among youth in African and other nations.